HSP70 and Its Cochaperone CPIP Promote Potyvirus Infection in Nicotiana benthamiana by Regulating Viral Coat Protein Functions - Hafren, Anders; Hofius, Daniel; Ronnholm, Gunilla; Sonnewald, Uwe; Makinen, Kristiina (The Plant Cell, 2010)
This study demonstrates that heat shock protein 70 (HSP70) together with its cochaperone CPIP regulates the function of a potyviral coat protein (CP), which in turn can interfere with viral gene expression. HSP70 was copurified as a component of a membrane-associated viral ribonucleoprotein complex from Potato virus A-infected plants. Downregulation of HSP70 caused a CP-mediated defect associated with replication. When PVA CP was expressed in trans, it interfered with viral gene expression and replication-associated translation (RAT). However, CP produced in cis interfered specifically with RAT. CPIP binds to potyviral CP, and overexpression of CPIP was sufficient to restore RAT inhibited by expression of CP in trans. Restoration of RAT was dependent on the ability of CPIP to interact with HSP70 since expression of a J-domain mutant, CPIP Delta 66, had only a minor effect on RAT. CPIP-mediated delivery of CP to HSP70 promoted CP degradation by increasing its ubiquitination when assayed in the absence of virus infection. In conclusion, CPIP and HSP70 are crucial components of a distinct translation activity that is associated with potyvirus replication.